Analisis Faktor yang Mempengaruhi Kasus Acute Flaccid Paralysis (Afp) di Indonesia dengan Menggunakan Regresi Poisson Tergeneralisasi - Rahmadeni Rahmadeni, M.Si (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2018)
AFP is an abbreviation of Acute Flaccid Paralysis which is a paralysis that occurs in children aged less than 15 years who are layering and occur suddenly (acute) not because of an accident. In the poisson regression analysis, the dependent variable must meet the assumption that the variance value is equal to the mean. However, in analysis of thing that sometime happen is the variance of the dependent variable is greate than the mean called the case overdispersion. In this study, researchers used the AFP case data in Indonesia in 2016. Parameter estimation using Maximum log likelihoood method. The  analysis result  in  this  study  showed  that  the  variables  which  are  influenced  to AFP is percentage of poor people (X1), percentage of population density (X2), percentage of immunization (X3), number of children more than one year old (X4).